Использование измерительного комплекса «КДЗ-1У» для оценки адекватности математической модели заземляющего устройства энергообъекта - Колиушко, Георгий Михайлович; Пличко, Андрей Валерьевич; Понуждаева, Елена Геннадьевна (НТУ "ХПИ", 2018)
Описана методика измерения напряжения прикосновения с использованием измерительного комплекса «КДЗ-1У». Описана конструкция применяемых струбцин и преимущества их использования. Изображены схемы соединения оборудования для определения напряжения прикосновения на территории электроустановки и для измерения переходного сопротивления потенциального электрода. Представлена последовательность действий при измерениях параметров в контрольных точках енергообъекта. Приведен образец документальной фиксации основных и дополнительных параметров для оценки адекватности математической модели заземляющего устройства.

The description of measurement procedure of contact voltage on the power equipment’s control points using measuring system "KDZ-1U", is the main goal of the project. The procedure is based on physical’s trials theory, ampere-voltmeter’s method and electromagnetic field theory. This procedure permits to obtain needed parameters for estimating mathematical model’s adequacy of power equipment’s grounding connection. Provided ground clamps’ design, and their features were described. Contact voltage measuring circuit on the actual power installation’s territory and transition resistance of polarizing electrode measurement schemes were shown. Operating procedure during parameter measurement of power equipment’s control points was represented. The prototype of documental recording of main and additional parameters for estimating mathematical model’s adequacy of grounding connection was provided.
Measurement system "KDZ-1U" usage in estimating mathematical model’s adequacy of power equipment’s grounding connection
Keywords: электроустановки; напряжение прикосновения; режим короткого замыкания; сопротивления контактного соединения; contact voltage; contact vomathematical model's adequacyltage; grounding grid system; mathematical model's adequacy